Colour terms in the Finno-Ugric languages - Räikkönen, Nea (Helsingin yliopisto, 2024)
This thesis examines various colour terms that can be found in the Finno-Ugric languages. The study aims to find and list the most salient colour terms equivalent to the 11 possible basic colour terms in these languages. Etymological background is also provided to varying degrees along with the results. There are 8 Finno-Ugric branches, and the study includes at least one language from each branch, bringing the total to 16 languages. Theoretical background introduces the definition of colour, Berlin and Kay’s basic colour theory, as well as the Finno-Ugric languages. The main source materials for collecting the colour terms vary from dictionaries to research papers to etymological databases, etc. The results of this study are analyzed by comparing them to Berlin and Kay’s basic colour term evolution theory. Recent colour terms and their origins will also be discussed. The main findings show how the colour terms for grey differ from the rest of the colour terms in the final stage of the basic colour term evolution theory. More research should be conducted to see whether this is exclusive to the Finno-Ugric languages, but the results in this study suggest that grey should have its own stage earlier in the basic colour term evolution theory. Another main finding is the lack of distinction between green and blue in North Khanty which should result in there not being distinct terms for colours in the later stages of the theory. North Khanty did, however, have distinct terms for the colours grey and pink. The results also show that the colour purple was missing the most colour terms which would indicate it being the least common or newest colour term in the Finno-Ugric languages. There are many borrowed lexemes in the colour terms. Recent colour terms in the minority languages spoken in Russia are mainly dominated by Russian loanwords, while older loanwords consist of various origins and ages, such as Germanic and Baltic in the Finnic languages, Scandinavian in the Saami languages, and Turkic in the Mari languages and ...